2016
DOI: 10.1097/md.0000000000005151
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related genetic polymorphisms affecting severe chemotherapy-induced neutropenia in breast cancer patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
3
16
2
Order By: Relevance
“…We found that, patients with CYP2J2 ∗ 7 allele, baseline grade 1 leukocytopenia, and grade 1 or 2 neutropenia, were significantly associated with increased risk of grade 3 or 4 hematologic toxicity. Low baseline WBC count as an important predictor for chemotherapy induced hematologic toxicity was consistent with previous reports (Lyman et al, 2003; Jenkins et al, 2012; Tsuji et al, 2016). However, CYP2J2 ∗ 7 was identified as new pharmacogenetic risk factors of chemotherapy induced hematologic toxicity in Ethiopian breast cancer patients.…”
Section: Discussionsupporting
confidence: 92%
“…We found that, patients with CYP2J2 ∗ 7 allele, baseline grade 1 leukocytopenia, and grade 1 or 2 neutropenia, were significantly associated with increased risk of grade 3 or 4 hematologic toxicity. Low baseline WBC count as an important predictor for chemotherapy induced hematologic toxicity was consistent with previous reports (Lyman et al, 2003; Jenkins et al, 2012; Tsuji et al, 2016). However, CYP2J2 ∗ 7 was identified as new pharmacogenetic risk factors of chemotherapy induced hematologic toxicity in Ethiopian breast cancer patients.…”
Section: Discussionsupporting
confidence: 92%
“…It is therefore intensively analyzed, both its expression and common variants, as the potential marker of cancer risk, chemotherapy responsiveness and side effects [ 28 , 29 ]. ERCC1 is also crucial for the repair of cyclophosphamide-induced DNA damage and cells, both normal and cancerous, and low-activity mutants may be hypersensitive to DNA crosslinking agents [ 30 ]. Two ERCC1 polymorphisms selected for this study, p.Asn118= (rs11615) in exon 4 and c.1510C>A (rs3212986) in 3’UTR are extensively studied in many cancers and chemotherapeutic regimes because of their negative influence on the stability and level of ERCC1 mRNA and on the protein expression [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst not the focus of this review, it is important to note that the role of pharmacogenetics in the risk of excessive toxicity (due to high levels of bioactivation of this cytotoxic drug) have also been assessed. Associations between CYP2C19 and/or CYP2B6 , as well as other pharmacogenes such as ALDH , GSTP1 and CYP3A4 , and the severity of neutropenia or premature ovarian failure have been reported …”
Section: Therapeutic Outcomesmentioning
confidence: 99%
“…Associations between CYP2C19 and/or CYP2B6, as well as other pharmacogenes such as ALDH, GSTP1 and CYP3A4, and the severity of neutropenia or premature ovarian failure have been reported. 40,65,67,[70][71][72][73][74][75]…”
Section: Therapeutic Outcomesmentioning
confidence: 99%